Ellagic acid attenuates liver toxicity induced by valproic acid in rats - Noha F. Abdelkader; Mohammed Elyamany; Amany M. Gad; Naglaa Assaf; Hala M. Fawzy; Wesam H. Elesawy (Elsevier, 2020)
Valproic acid is a commonly used drug for many psychiatric disorders, particularly for epilepsy. However, it has been reported that its use is associated with possible side effects including hepatotoxicity.The present study investigated the hepatoprotective effect of ellagic acid against valproic acid-induced hepatotoxicity in rats.Ellagic acid (60 mg/kg/day; p.o) was treated for one week, followed by concomitant injection of valproic acid (250 mg/kg/day; i.p.) for another 14 consecutive days to induce hepatocellular damage in adult Sprague-Dawley rats.Valproic acid showed a marked increase in serum enzyme activities, AST, ALT, ALP and GGT. In addition, it significantly increased MDA and NO along with a marked decline in reduced GSH content. At the same time, valproic acid administration resulted in marked elevation in hydroxyproline, TNF-α production and NF-kB expression. These results were confirmed by histopathological examination.Treatment with ellagic acid markedly attenuated valproic acid-induced hepatic injury in rats. Keywords: Valproic acid, Hepatotoxicity, Oxidative stress, Ellagic acid, Hepatocellular damage